Energy Security: Theoretical Interpretations and Quantitative Evaluation - Zhiznin, Stanislav Z.; Timohov, Vladimir M.; Dineva, Velislava (International Journal of Energy Economics and Policy, 2020)
Although the question of energy security is regarded as an integral part of the contemporary political agenda, there is no single definition that has been agreed among the international community. The term itself has been evolving for more than 40 years of use. This article reviewes and compares existing definitions of the concept at global, regional, and national levels as well as from scientific point of view. It is commonly accepted that security is related to risk. Identifying and measuring energy security risks is a difficult task as the term contains elements whose meaning often depends on the context. Since the energy system cannot be fully protected, it is appropriate to consider energy security as a risk management problem. This article analyses existing energy security assessment literature and proposes a complemented approach for measuring and evaluating national energy security. Keywords: Energy security, energy policy, energy system, risk, uncertainty, indicators, assessment framework. JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.8950